Hierarchical Assembly of CaMoO4 Nano-Octahedrons and Their Photoluminescence Properties - Longo, Valeria M. [UNESP]; Cavalcante, Laecio S. [UNESP]; Paris, Elaine C. [UNESP]; Sczancoski, Julio C. [UNESP]; Pizani, Paulo S.; Li, Maximo Siu; Andres, Juan; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (Amer Chemical Soc, 2011)
Hierarchical assemblies of CaMoO4 (CM) nano-octahedrons were obtained by microwave-assisted hydrothemial synthesis at 120 degrees C for different times. These structures were structurally, morphologically and optically characterized by X-ray diffraction, micro-Raman spectroscopy, field-emission gun scanning electron microscopy, ultraviolet-visible absorption spectroscopy and photoluminescence measurements. First-principle calculations have been carried out to understand the structural and electronic order-disorder effects as a function of the particle/region size. Supercells of different dimensions were constructed to simulate the geometric distortions along both they and z planes of the scheelite structure. Based on these experimental results and with the help of detailed structural simulations, we were able to model the nature of the order-disorder in this important class of materials and discuss the consequent implications on its physical properties, in particular, the photoluminescence properties of CM nanocrystals.